Conceptual Framework for Cyber Competence of Military Institution Personnel in the Digital Age: A Literature Review - Rahmat Kurniawan; Eko Prasojo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Digital transformation has a disruptive effect on organizations with the most standard format, namely military organizations. The TNI AD must master the latest technology, including information technology and war equipment, as a response to digital transformation. The war that occurs is no longer related to physical war but the war caused by the flow of technology and information. This article discusses a conceptual framework that can be adapted to understand cyber competence, the factors that influence cyber competence, and strategies for strengthening cyber competence that can be adapted to support the role of the Indonesian Army in maintaining network and infrastructure security from cyber attacks. A qualitative approach using a literature study is applied in this case. The results show that in carrying out the cyber job role, the personnel responsible for the position must have the knowledge, skills, aspects of self-image, social motives, traits, mindset (thought pattern), frame of mind, ways of thinking, feeling, and acting (way of thinking, feeling, and acting) related to the cyber job role description. Personnel's cyber competence will be influenced by education, training, personal characteristics, and environment. To improve the cyber competence of personnel, strategies that can be carried out are in the form of needs analysis, development of core competencies, and changes to innovative work designs.